Adaptações dos contos clássicos infantis: contribuições para uma representatividade negra - Santos , Rosilânea Niedja Soares Costa dos (2020)
This research aims at focusing on literary reading in a classroom of the fifth year in a municipal school in João Pessoa, located in a quilombola territory in the same city. We have chosen book adaptations of classic children's stories so as to conduct interventional actions, once we believe that these short texts can significantly contribute to a more reflective and critical reader formation. The choices concerning the adaptations were not randomly made, and the characters carry a very strong black identity representation. Aspects related to identity self-recognition and the school condition, which is in a quilombola community and has still constituted, in its majority, a student body formed by blacks and browns, reaffirmed the desire to foster reflections and impressions about identity, acceptance and overcoming of challenges imposed by racism. We intend, by means of literary literacy, to awaken the taste and pleasure for reading, impressing the vision that reading is a tool for change, for social interactions and for broadening horizons. As to the methodologial aspect, this work is characterized as an action research. The intervention took place by means of thematic workshops supported by the basic sequence of Cosson (2014). For doing so, we analyzed three adaptations of classic fairy tales: A princesa e a ervilha (2016), Rapunzel e o Quibungo (2015), and Cinderela e Chico Rei (2015), focusing on the possible contributions that these works are providing for a black self-affirmation. Our analyzis are based on discussions as we consider Candido (1995), Coelho (2012), Colomer (2003), Cosson (2014), Cuti (2010), Hall (2015), Zilberman (2012) and others that interest our proposal.